Development and evaluation of a RT-qPCR assay for the detection of Orthoflavivirus wesselsbronense from formalin-fixed, paraffin-embedded tissues from sheep and cattle - Odendaal, Lieza (University of Pretoria, 2024)
Dissertation (MSc (Veterinary Tropical Diseases))--University of Pretoria, 2024.